Dexmedetomidine Enhances Autophagy via α2-AR/AMPK/mTOR Pathway to Inhibit the Activation of NLRP3 Inflammasome and Subsequently Alleviates Lipopolysaccharide-Induced Acute Kidney Injury - Yang, Tianyuan; Feng, Xiujing; Zhao, Yuan; Zhang, Haiyang; Cui, Hailin; Wei, Mian; Yang, Haotian; Fan, Honggang (Frontiers in Pharmacology, 2020)
Backgroud. Acute kidney injury (AKI) is a severe complication of sepsis; however, no effective drugs have been found. Activation of the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome is a major pathogenic mechanism of AKI induced by lipopolysaccharide (LPS). Autophagy, a process of intracellular degradation related to renal homeostasis, effectively restricts inflammatory responses. Herein, we explored the potential protective mechanisms of dexmedetomidine (DEX), which has confirmed anti-inflammatory effects, on LPS-induced AKI. Methods. AKI was induced in rats by injecting 10 mg/kg of LPS intraperitoneally (i.p.). Wistar rats received intraperitoneal injection of DEX (30 µg/kg) 30 min before an intraperitoneal injection of LPS. Atipamezole (ATI) (250 µg/kg) and 3-methyladenine (3-MA) (15 mg/kg) were intraperitoneally injected 30 min before DEX injection. Results. DEX significantly attenuated renal injury. Furthermore, DEX decreased activation of the NLRP3 inflammasome and expression of interleukins 1β and 18. In addition, autophagy-related protein and gene analysis indicated that DEX could significantly enhance autophagy. Finally, we verified the pharmacological effects of DEX on the 5'-adenosine monophosphate-activated protein kinase (AMPK)/mechanistic target of rapamycin (mTOR) pathway. Atip and 3-MA significantly reversed the protective effects of DEX. Conclusions. Our results suggest that the protective effects of DEX were mediated by enhanced autophagy via the α2-adrenoreceptor/AMPK/mTOR pathway, which decreased activation of the NLRP3 inflammasome. Above all, we verified the renal protective effects of DEX and offer a new treatment strategy for AKI.